Student Perceptions of the Effectiveness of Field Experience Practicum in the Department of Islamic Community Development - Abdullah, Abdullah; Tanjung, Muaz (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2024)
Field experience practicum in the Department of Islamic Community Development often faces challenges that result in gaps between theory and practice, as well as suboptimal impact on students and communities. This study aims to explore students' perceptions of practicum effectiveness, focusing on influencing factors and challenges faced. The methods used included interviews with students and analysis of relevant documents to collect data on their experiences and recommendations. The results showed that students faced various challenges, such as time constraints, support from authorities at practicum sites, and gaps between theory and practice. The implications of this study indicate the need for a more holistic approach in practicum design in order to improve the quality of education and the relevance of the curriculum, as well as provide greater benefits for students and society. Thus, the results of this study are expected to guide educational institutions in improving practicum experiences in the future.